Impact of childhood burn injuries on breastfeeding: a case report - Zurraini Arabi; Ezura Madiana Md Monoto; Agusmanan Bojeng (BMC, 2019)
Abstract Background Pre-pubescent girls with chest burns are at risk of complication associated with scarring and impairment in breast development. This case illustrates how burn injuries in childhood in a first-time mother have affected her in terms of breastfeeding. Case presentation In May 2015, a 20 year old first-time mother at 36 weeks gestation was seen in a district health clinic in Kuching, Sarawak in regards to her ability to breastfeed. She had a history of a flame burn at the age of 5 years old to her chest, abdomen, upper limb and part of her trunk. A skin graft was done on her whole chest and abdomen. Despite the injuries, she had pubertal and antenatal breast development. Her abdomen was able to stretch to accommodate her pregnancy. Physical examination showed a pregnancy which corresponded to date. The skin over her chest and abdomen appeared tight with areas of hyperpigmentation and hypopigmentation due to scarring from the skin graft. Breast tissues were palpable over her chest. The areola and nipple tissue were completely absent with complete scarring of the nipple-areolar complex. There was no duct opening to the areola for milk expression or leakage. Counselling regarding her breastfeeding issues was done. She delivered her baby at full term via spontaneous vaginal delivery with no complication. Oral cabergoline 1 mg was given on the first day postpartum. The baby was given infant formula via bottle feeding as the feeding method of choice. Conclusion Counselling plays an important part in the management of a mother with breastfeeding difficulty. Allaying the possible guilty feelings of not being able to breastfeed will fulfil the emotional gap which may arise in a mother with these challenges.